The Influence of Ewom on Decisions to Visit Entre-preneurial Companies (Case Study of The Great Asia Africa Tourism Medium Enterprises) - arif hernowo; Arianis Chan; Margo Purnomo (Politeknik Negeri Bengkalis, 2022)
In the current era, people will compete to share their travel experiences to get feedback from their friends or colleagues. This story is an Electronic word of mouth (E-WOM) that can have a positive or negative impact on the company. E-WOM is any statement both positive and negative made by potential, actual, or past consumers about a product or company made to a large number of people or institutions via the internet (Hennig-Thurau, 2004 in Prasad, et al, 2017) . This is also used by The Great Asia Africa Lembang, one of the tourist destinations in West Bandung Regency that uses social media as a medium to promote the uniqueness of existing attractions. This study examines the effect of Electronic Word Of Mouth (E-WOM) on the decision to visit The Great Asia Africa Lembang, West Bandung Regency. The method used in the research in this journal uses quantitative methods that are analyzed by alternative partial least squares (PLS) with a sample of 270 respondents. The findings in this study indicate the influence of Electronic Word Of mouth (E-Wom) on the decision to visit tourists. The limitation in this study is only using a sample of Instagram followers from The Great Asia Africa, so it is necessary to expand the reach of the population to get more diverse responses. From the results of the research obtained, it shows that Ewom's assessment is still in the good category so that it can be improved to be very good by increasing the productivity of the content created and conducting periodic research to find out the effectiveness of the influence of Electronic Word of Mouth.